PENGARUH SUBTITUSI JAGUNG MANIS TERHADAP KUALITAS DADIAH - fatmawati fatmawati fatmawahttp://jpk.ppj.unp.ac.id/index.ti; Anni Faridah; Elida Elida (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
The purpose of this study was to analyze the effect of sweet corn substitution by 0%, 25%, 50% and 75% on the quality of color, smell, texture and taste of the amount of buffalo milk used. This type of research belongs to a kind of pure experiment using a completely randomized design method of one factor. This research was conducted in Kanagarian Gadut Pakan Raba'a Jorong Lareh Nan Panjang Payakumbuh. The research instrument used is organoleptic test format given to 5 expert panelists namely dadiah farmers. The data obtained is tabulated and do Variant Analysis (ANAVA), if Fcount> Ftable then proceed with Duncan test. The results of the data analysis obtained the highest overall score, yellow color quality is 4.00 (X3), quality smells typical dadiah 4.00 (X0), sweet corn quality 3.33 (X3), soft texture quality 3.80 (X0), solid texture quality 4.00 (X3) ,quality of sweet corn flavor 3.53 (X3) and acid taste 3,73 (X3).